Innovations at the edge: how local innovations are established in less favourable environments - Ralph Richter (Urban Research & Practice, 2020)
Local innovation research often focuses on big cities and creative places. However, novel developments also emerge in provincial cities and in interactions between (social) entrepreneurs and policymakers. This article shows, by way of two case studies in Greece and Poland and an interpretive policy analysis, how local innovations are established in seemingly less innovation-friendly cities. It reveals that it is not the innovative product itself that faces opposition, but the new ways of collaborative action that pave the way for the novel development. Overcoming resistance takes place in communicative negotiation processes and benefits from shared problem construction.
Keywords: 710; Local innovations; provincial cities; innovation semantics; rules of the game; city-related knowledge